#TITLE_ALTERNATIVE# - ANTHONY (NIM : 15112006), GERRY
Global climate change is causing the rising of hot air temperature that impacts human health. Land Surface Temperature as one of the products of remote sensing is used as the data to represent temperature of the air in a wide area. This study aimed to determine the relationship between between LST and heat-related illnesses in the Bangkok Metropolitan Region. The method used in this study is statistical analysis methods that define the coefficient of determination to determine the contribution of the influence of variables one with two variables and the correlation coefficient to determine the relationship between the two variables. The results in this study show the coefficient of determination are 0.93 in province of Nonthaburi with the correlation coefficient is 0.96, 0.43 in the province of Samut Sakhon with the correlation coefficient is 0.66, 0.37 in the province of Nakhon Pathom with the correlation coefficient is 0.57, 0.38 in province of Pathum Thani with the correlation coefficient is 0.61, and 0.11 in the province of Samut Prakan with the correlation coefficient is 0.33. Furthermore, the results show that there are variation of influences and relationships between LST and heat-related illness in Bangkok Metropolitan Region